Competition between physical and electronic content retailers - Yuta Kittaka; Noriaki Matsushima; Fuyuki Saruta (Osaka University, Institute of Social and Economic Research (ISER), 2021)
We investigate a model in which a monopoly supplier distributes two types of its product through a traditional retailer with a wholesale price contract and an online retailer with an agency contract. Because such an agency contract eliminates the double marginalization problem, the online retailer has a cost advantage over the traditional retailer. Given the advantage of the online retailer, we also consider a possible request by the traditional retailer: the retail price of the online retailer is not smaller than the wholesale price for the traditional retailer. We obtain the following results. An increase in the online retailer's bargaining power over the supplier benefits the two retailers but harms the supplier. Under the request to protect the traditional retailer, the wholesale price is strictly higher than that in the baseline model. The retailers' equilibrium prices are also strictly higher than those in the baseline model. The request benefits the supplier and the online retailer, but harms the traditional retailer.
Keywords: L22; L13; C72; C78; 330; Agency contract; Price-quantity competition; Dual-channel supply chain; Royalty rate